2020
DOI: 10.1002/hec.3996
|View full text |Cite
|
Sign up to set email alerts
|

Social connections and tertiary health‐care utilization

Abstract: The use of tertiary health care by socially proximate peers helps individuals learn about program and treatment procedures, signals that using such care is socially appropriate, and could support the use of formal health care, all of which could increase program utilization. Using complete administrative claims data from a publicly financed tertiary care program in India, we estimate that the elasticity of first‐time claims with respect to claims by members of caste groups within the village is 0.046, with sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 32 publications
4
14
0
Order By: Relevance
“…In this paper, we use the approach of ‘ random matching within samples’ to measure social networks (Conley & Udry 2010; Maertens 2010; Maertens & Barrett 2012; Santos & Barrett 2010). This method can also lead to an omitted variable bias if an important node of a network is ignored by the random matching.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this paper, we use the approach of ‘ random matching within samples’ to measure social networks (Conley & Udry 2010; Maertens 2010; Maertens & Barrett 2012; Santos & Barrett 2010). This method can also lead to an omitted variable bias if an important node of a network is ignored by the random matching.…”
Section: Methodsmentioning
confidence: 99%
“…The author cautions that ignoring these interactions between farmers could lead one to overestimate the effect of household characteristics on adoption decisions. In a similar study, Conley and Udry (2010) found that in the case of pineapple cultivation in Ghana, farmers adjust their inputs in accordance with information from neighbours who were successful in earlier periods. The authors highlight the importance of social learning, and the network connections through which information flows, in farmers’ cultivations decisions.…”
Section: The Literaturementioning
confidence: 95%
See 3 more Smart Citations